The course of tuberculosis against pregnancy - A. V. Mordik; A. V. Kravchenko; G. A. Valeeva; L. V. Puzyreva (Кубанский научный медицинский вестник, 2014)
The analysis of a course of specific process against pregnancy at 59 patients is carried out, 25 women at whom tuberculosis was revealed during the real pregnancy, made group of comparison of them the main group - 34 women at whom pregnancy came against the course of active tuberculosis. it is established that pregnancy negatively influences the current and a tuberculosis outcome, can lead to complications and disease progressing. By means of the cluster analysis it is proved that the widespread form of tuberculosis and refusal of antitubercular therapy can lead to a lethal outcome within the first 3 years after the delivery.